1996
DOI: 10.1007/bf02523416
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic modification of evening primrose oil: Incorporation of n−3 polyunsaturated fatty acids

Abstract: Immobilized lipase SP435 from Candida antarctica was used as a biocatalyst for the modification of the fatty acid composition of evening primrose oil by incorporating n-3 polyunsaturated fatty acid (PUFA) and eicosapentaenoic acid (EPA). Transesterification (ester-ester interchange) was conducted in organic solvent or without solvent, with EPA ethyl ester (EEPA) as the acyl donor. Products were analyzed by gas-liquid chromatography (GLC). After 24-h incubation in hexane, the fatty acid composition of evening p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
23
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 16 publications
7
23
0
1
Order By: Relevance
“…In present study, the incorporation of ALA into olive oil increased by increasing the molar ratio of ALA: olive oil. Other investigators have also reported that the incorporation of n-3 fatty acid into seed oil raises by increasing the substrate molar ratio [11,22]. Also, it has been stated that incorporation rate can be improved by choosing high substrate molar ratios while reducing the reaction time, but Jennings and Akoh [27] have pointed out a significant modification in large scale, using excess amounts of n-3 fatty acid had resulted in lipase inhibition and decreased in product yield while removing excess fatty acids.…”
Section: Effect Of Ratio Of Ala: Olive Oil For Enrichment Of Olivementioning
confidence: 93%
See 1 more Smart Citation
“…In present study, the incorporation of ALA into olive oil increased by increasing the molar ratio of ALA: olive oil. Other investigators have also reported that the incorporation of n-3 fatty acid into seed oil raises by increasing the substrate molar ratio [11,22]. Also, it has been stated that incorporation rate can be improved by choosing high substrate molar ratios while reducing the reaction time, but Jennings and Akoh [27] have pointed out a significant modification in large scale, using excess amounts of n-3 fatty acid had resulted in lipase inhibition and decreased in product yield while removing excess fatty acids.…”
Section: Effect Of Ratio Of Ala: Olive Oil For Enrichment Of Olivementioning
confidence: 93%
“…Recently, many efforts have been carried out in transesterification or inter-esterification reactions to Transesterification Reaction: A small scale modify and enrich the content of n-3 PUFA in vegetable transesterification reaction was conducted in 50 ml oil, melonseed oil, borage oil and evening primrose oil round bottom capped flask. According to author with implementation of biocatalysts such as lipases previous work [13], -linolenic acid (ALA) which is used [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Akoh e colaboradores 55 descreveram a reação de transesterificação entre óleo de prímula (ácido γ-linolênico) e éster etílico de EPA como doadores de grupo acil, catalisada por lipase imobilizada de Candida antarctica. A incorporação de EPA foi de 34%, enquanto os níveis de ácido γ-linolênico não sofreram mudanças significativas, o que resultou em uma modificação favorável na taxa de ω3/ω6 de 0,01 para 0,60 após reação de transesterificação.…”
Section: Interesterificaçãounclassified
“…It could be useful to use this oil as a model oil when incorporating long-chain EFA into MCT. Recently, the incorporation of n-3 PUFA, especially EPA and DHA, into melon seed oil (13), vegetable oils (14), borage oil (15)(16)(17)(18), evening primrose oil (18,19), and trilinolein (20) has been reported. Synthesis of SL containing MCFA in the sn-1,3 positions and an unsaturated LCFA in the sn-2 position of the glycerol backbone using 1,3-regiospecific lipases was recently reported by Soumanou et al (21).…”
mentioning
confidence: 99%